Far Beyond Google Translate: Natural Language Processing (NLP) in Translation and Translatology - Okulska, Inez (Porównania, 2020)
The more technological development, the greater the participation of the human – in formulating tasks and problems, supervising and improving automated processes and interpreting their outcomes. The hierarchy is preserved, humans are still indispensable, but it does not mean that in certain areas of machinery the potential does not really exceed that of the human and that this advantage is not worth exploiting. Natural language processing (NLP) is not a young field, but in recent years, thanks to the thrive of deep learning methods, data and knowledge mining or new human-machine interfaces, computer text analysis is experiencing a real renaissance. As far as translation is concerned, it is mostly algorithms for machine translation that are being discussed. This article, on the other hand, presents a slightly broader spectrum of the translation process and looks at the accompanying elements (such as criticism) in which the use of NLP methods may bring new and interesting results. Results which, due to limited computing power, humans are unable to achieve. The discussion in the paper covers such aspects as the vector representation of language, stylometry and its application, or the analysis of large data sets – all for the purposes of translation and translatology.